2021
DOI: 10.3390/ijms22116079
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fucosylated SERPINA1 as a Novel Plasma Marker for Pancreatic Cancer Using Lectin Affinity Capture Coupled with iTRAQ-Based Quantitative Glycoproteomics

Abstract: Pancreatic cancer (PC) is an aggressive cancer with a high mortality rate, necessitating the development of effective diagnostic, prognostic and predictive biomarkers for disease management. Aberrantly fucosylated proteins in PC are considered a valuable resource of clinically useful biomarkers. The main objective of the present study was to identify novel plasma glycobiomarkers of PC using the iTRAQ quantitative proteomics approach coupled with Aleuria aurantia lectin (AAL)-based glycopeptide enrichment and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…AAT acts on FN1 through Snail in colon and gastric cancer, resulting in epithelial-mesenchymal transformation, in turn, promoting cancer progression and metastasis [18,20]. In view of the elevated levels of AAT in both chronic pancreatitis and PDAC samples, we speculate that AAT also induces progression of chronic pancreatitis to PDAC through this mechanism [15,21]. The collective findings indicate that AAT not only is an acute phase reactive protein but also plays an important role in the acute pancreatitis-chronic pancreatitis-pancreatic cancer axis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…AAT acts on FN1 through Snail in colon and gastric cancer, resulting in epithelial-mesenchymal transformation, in turn, promoting cancer progression and metastasis [18,20]. In view of the elevated levels of AAT in both chronic pancreatitis and PDAC samples, we speculate that AAT also induces progression of chronic pancreatitis to PDAC through this mechanism [15,21]. The collective findings indicate that AAT not only is an acute phase reactive protein but also plays an important role in the acute pancreatitis-chronic pancreatitis-pancreatic cancer axis.…”
Section: Discussionmentioning
confidence: 95%
“…However, CA19-9 is also increased in benign pancre-atic and biliary diseases, such as obstructive jaundice, pancreatitis, cholangitis, and cancer of the stomach, colon, ovary, uterus, liver, and other organs [45,46]. In addition, 8-10% Caucasians with Lewis A-B genotype do not express CA19-9, indicative of limitations as a biomarker of pancreatic cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was shown the higher levels of α-1-antitrypsin in nonrelapsing Hodgkin lymphoma (HL) compare to relapsing HL [48]. As far as posttranslational modification (PTMs) and proteoforms, different glycosylated patterns of serpin A1 were observed in lung cancer and PDAC patients [49,50]. Serpin A1 has 3 known splice-isoforms and 8 potential isoforms that are computationally mapped.…”
Section: Alpha-1-antitrypsin (A1at_human)mentioning
confidence: 99%
“…SERPINA1 (Serpin family A member 1) encodes a well-known elastase inhibitor, alpha-1 antitrypsin (AAT). Previously, Wiseman and his colleagues reported that SERPINA1 can be diagnostic biomarker of thyroid cancer [ 112 ], and SERPINA1 has been recently reported to be involved in several other cancers including gastric, liver, pancreas, breast, lung, and ovarian cancers [ 113 , 114 , 115 , 116 , 117 , 118 ]. Moreover, Gao and his colleagues suggested that SERPINA1 is one of key genes in brain metastasis from lung adenocarcinoma [ 119 ].…”
Section: Hsf2 Affects Cancer Development and Progressionmentioning
confidence: 99%